2020
DOI: 10.1177/2325967120946326
|View full text |Cite
|
Sign up to set email alerts
|

Failure Rates of 5-Strand and 6-Strand vs Quadrupled Hamstring Autograft ACL Reconstruction: A Comparative Study of 413 Patients With a Minimum 2-Year Follow-up

Abstract: Background: Anterior cruciate ligament reconstruction (ACLR) with hamstring autograft has gained popularity. However, an unpredictably small graft diameter has been a drawback of this technique. Smaller graft diameter has been associated with increased risk of revision, and increasing the number of strands has been reported as a successful technique to increase the graft diameter. Purpose: To compare failure rates of 5-strand (5HS) and 6-strand (6HS) hamstring autograft compared with conventional 4-strand (4HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The mean equivalent graft diameter of HT8 was 10 mm in this study, which was supposed to be stronger than the conventional 4‐ to 6‐stranded grafts. Attia et al [44] revealed that the graft failure rates of 4‐, 5‐, and 6‐stranded autologous hamstrings for SB‐ACLR were 9.1%, 2.3%, and 2.7%, with mean graft diameters of 8.3, 9.1, and 9.0 mm, respectively. Zhao et al [24] reported that residual pivot shift after DB‐ACLR was detected in 12.1% of patients using HT4 autografts and 2.9% of patients using HT8 autografts with mean equivalent diameters of 7.8 and 9.7 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The mean equivalent graft diameter of HT8 was 10 mm in this study, which was supposed to be stronger than the conventional 4‐ to 6‐stranded grafts. Attia et al [44] revealed that the graft failure rates of 4‐, 5‐, and 6‐stranded autologous hamstrings for SB‐ACLR were 9.1%, 2.3%, and 2.7%, with mean graft diameters of 8.3, 9.1, and 9.0 mm, respectively. Zhao et al [24] reported that residual pivot shift after DB‐ACLR was detected in 12.1% of patients using HT4 autografts and 2.9% of patients using HT8 autografts with mean equivalent diameters of 7.8 and 9.7 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For greater success in ACL reconstruction with ST-G graft, this graft must have a diameter equal to or greater than 8 mm, supporting greater loads and reducing the risk of rupture. 1 Some techniques have already been described to increase the diameter of the graft, such as a quintuple graft in which ST is folded 3 times when the length of the graft is sufficient. 5 There is also the described possibility of enlarging the graft using a tissue bank allograft.…”
Section: Video Transcriptmentioning
confidence: 99%
“…However, we did not collect data to find how many surgeons were directly taking STT and gracilis tendon together. Although a smaller diameter graft is at higher risk for rupture [11], the pertinent question is whether increasing graft diameter (> 8 mm) would result in a decreased rate of graft rupture or not, as several studies do not demonstrate any significant clinical benefit of increasing diameter above eight mm [13,14]. Hence the clinical advantage of increasing the diameter of 'soft graft' beyond 8 mm should be further investigated with well-designed studies.…”
Section: B) Intra-operative Trendsmentioning
confidence: 99%